Nghiên cứu khảo sát các phương pháp tổng hợp chất kích thích sinh trưởng thực vật axit indol-3-butyric (IBA) - Hoằng và cộng sự, Đào Văn (Vietnam Journal of Chemistry, 2014)
The indole-3-butyric acid (IBA) is an important plant growth stimulator. Its synthesis has been carried out by different ways. Some methods for preparation of IBA were discussed. In this work, the compound was synthesized by two methods: reacting indol with g-butyrolactone and gramine with diethylmalonate. However, the reaction of indol with g-butyrolactone in tetralin as solvent is realized in the more acceptable conditions of pressure and temperature therefore can continue the study for application in practice.